Non-Invasive Quantification of Layer-Specific Intrinsic Fluorescence From Mucosa of the Uterine Cervix Using Monte-Carlo-Based Models - Lin, Guo-Sheng; Tu, Shih-Cheng; Mok, Chong-Ian; Huang, Tsan-Hsueh; Chen, Chi-Hau; Wei, Lin-Hung; Sung, Kung-Bin (Frontiers in Physics, 2022)
Fluorescence spectroscopy has been demonstrated to non-invasively detect changes related to precursors of epithelial cancers, which include decreased fluorescence emission from collagen crosslinks in the connective tissue and increased fluorescence emission from reduced nicotinamide adenine dinucleotide in the epithelial tissue. Extensive efforts have attempted to extract the intrinsic fluorescence intensity and/or spectral shape from fluorescence spectra measured at the tissue surface. However, previous methods have assumed the tissue to be homogeneous, which may lead to significant errors for mucosa at the uterine cervix consisting of an epithelial layer of about 0.1-0.6 mm in thickness. We implemented two-layer forward Monte Carlo models to predict diffuse reflectance and fluorescence intensities at the surface of cervical mucosa given tissue absorption, scattering, and fluorescence properties. The absorption and scattering coefficients of the upper epithelial layer and underlying connective tissue, as well as the epithelial thickness, were estimated from diffuse reflectance spectra using iterative curve fitting. The estimated parameters were used by the fluorescence forward model to obtain quantities needed to relate the intrinsic fluorescence of tissue fluorophores to measured fluorescence intensity. The emission spectra of tissue fluorophores were modeled by skew normal functions, and together with the efficiency of the fluorophores were extracted by fitting the modeled fluorescence spectra to measured spectra using the genetic algorithm. The performance of the proposed method was evaluated with simulated spectra and compared to that of using conventional one-layer forward models. The results showed that the proposed method is more accurate in estimated parameters and fitting residuals than the one-layer models. Feasibility of the proposed method was demonstrated by extracting layer-specific intrinsic fluorescence from the cervical mucosa of human subjects in vivo. The ability to more accurately estimate layer-specific intrinsic fluorescence from cervical mucosa could aid the detection of precancers in the cervix as well as other sites including oral and esophageal mucosae.